The right to property in commonwealth constitutions - Allen, Tom, 1959- (Cambridge studies in international and comparative law (Cambridge, England : 1996), 2000)
First book to examine constitutional rights to property in Commonwealth countries. Although many Commonwealth judges use comparative law in resolving constitutional cases, very few books have been written on comparative law in the Commonwealth. This book presents both practical and theoretical analyses, together with the historical background.